Strategi Inquiry Dalam Mengajarkan Toleransi Beragama di SMP IT Aziziyah Binjai - Arlina Arlina; Nur Haliza Dalimunthe; Nurul Habibatul Hidayah; Siti Rahmi Batubara; Cahaya Maharani Sitompul (STIT Sirojul Falah Bogor, 2023)
This study aims to find out how the inquiry learning strategy is applied to Islamic Religious Education subjects with the theme of religious tolerance. This study uses a qualitative phenomenological method with data collected through reading materials which are then carried out by observations and interviews by researchers who go directly to the field. Data is processed and analyzed by reducing data, presenting data and drawing conclusions. The following are the results of this study; inquiry strategy in applying inquiry learning to the subject of tolerance, namely, 1) the teacher provides opportunities for students to ask questions about intolerance cases in the form of rampant cases of blasphemy, treatment or discrimination based on ethnicity, religion, race, gender, and so on -others, 2) the teacher forms small groups for students 5-6 people, 3) the teacher directs them to carry out discussions and draw conclusions from the problem of material tolerance by linking the basis of God's word in the Qur'an. Besides that, the development of learning is in the form of observing the material studied with the development of society. The results of this study will have implications for the development of a 'research-based learning model theory in tolerance learning' in Islamic religious education. Keywords: Inquiry Learning Model, Islamic Religious Education, Educators, Students, Tolerance.